The Effect of Biofertilizer under Drought: Vitamin C, Starch Content, Biomass and Root Anatomy of Shallot (Allium cepa L.) - Dwi Umi Siswanti; Nurrisma Ika Lestari; Marlyn Dian Laksitorini (Majalah Obat Tradisional, 2026)
Shallots (Allium cepa L.) is a plant that requires sufficient water and is susceptible to drought stress. The use of biofertilizer is employed because it contains microorganisms to enhance nutrient availability and assist plant growth under abiotic stress. The biofertilizer used in this study is the Siswanti formula (EnWie Biofertilizer) which contains Bacillus sp., Lactobacillus sp., Saccharomyces sp., Streptomyces sp., Pseudomonas, Azospirillum, Azotobacter, Rhizobium and Trichoderma sp. This study aims to analyze the physiological and anatomical responses of shallot bulbs following the application of biofertilizer under drought stress. The doses of biofertilizer used were 10 L/ha, 15 L/ha, and 20 L/ha with field capacity levels of 25%, 50%, 75%, and 100%. Parameters tested included vitamin C content, starch content, cortex thickness anatomy and dry weight of shallot roots. The method used to determine the vitamin C content was UV-VIS spectrophotometry, while the starch content research used the Nelson-Smogy method. The method used in making shallot root specimens was the embedding method. The results of this study showed that the application of biofertilizer affects the physiology and anatomy of Allium cepa L. under drought stress. The application of 15 L/ha biofertilizer increases vitamin C content, starch content, and cortex thickness. Meanwhile, 10 L/ha biofertilizer increases root dry weight.